2010
DOI: 10.1124/jpet.110.174011
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Triple Reuptake Inhibitor JZAD-IV-22 Exhibits an Antidepressant Pharmacological Profile without Locomotor Stimulant or Sensitization Properties

Abstract: Triple reuptake inhibitors (TRIs) that block the dopamine transporter (DAT), norepinephrine transporter, and serotonin transporter are being developed as a new class of antidepressant that may have better efficacy and fewer side effects compared with traditional antidepressants. We describe a novel TRI, 2- (DOV 216,303), a TRI shown to be an effective antidepressant in a clinical trial, shows reuptake inhibition similar to that of JZAD-IV-22 in vitro. Furthermore, both JZAD-IV-22 and DOV 216,303 increase leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…No data are available on the sexual side effect profile of TRIs, but a recent trial with a TRI (the DOV 216,303 isomer amitifadine) showed no worsening of sexual functioning after chronic treatment of depressed patients [37]. The preclinical data (Figure 3 left column, middle) confirm the lack of sexual side effects of DOV 216,303 at doses that exert antidepressant effects in animal models of depression [36,[38][39][40]. This clearly suggests that 5-HT mediated inhibition of sexual behavior can be overcome by stimulating dopaminergic neurotransmission via dopamine transporter (DAT)-blockade, although a role for noradrenaline cannot be excluded.…”
Section: Sexual Dysfunctionsupporting
confidence: 49%
“…No data are available on the sexual side effect profile of TRIs, but a recent trial with a TRI (the DOV 216,303 isomer amitifadine) showed no worsening of sexual functioning after chronic treatment of depressed patients [37]. The preclinical data (Figure 3 left column, middle) confirm the lack of sexual side effects of DOV 216,303 at doses that exert antidepressant effects in animal models of depression [36,[38][39][40]. This clearly suggests that 5-HT mediated inhibition of sexual behavior can be overcome by stimulating dopaminergic neurotransmission via dopamine transporter (DAT)-blockade, although a role for noradrenaline cannot be excluded.…”
Section: Sexual Dysfunctionsupporting
confidence: 49%
“…Remarkably, neither noradrenaline (NRI), serotonin (SSRI) nor mixed NE/5-HT reuptake blockers (SNRI) were able to substitute for the tramadol DS, whereas NRIs, but not SSRIs were able to shift the dose-response curve to the left. It is well known that SSRIs are notoriously difficult to train as a DS in rats (Olivier 2015) whereas NRIs create trainable cues (Caldarone et al 2010;Dekeyne et al 2001). Tramadol, via its (-)-enantiomer and (-)-metabolite, has norepinephrine reuptake inhibiting effects that may contribute to its sexual inhibitory effects at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…[13]. Interestingly, DOV 216,303 exerted these addiction-like effects at doses higher than the effective doses in depression models (5-10 mg/kg versus 20-100 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent rat study showed that DOV 216,303 partially substituted for cocaine in a drug discrimination test and caused a sensitization response at high doses although the doses used in these experiments were higher than the effective doses in depression models [13]. To further explore and characterize the possible abuse potential of DOV 216,303, we compared its effects with cocaine in addiction-related mouse models: acute self-administration, conditioned place preference as well as drug-induced hyperlocomotion.…”
mentioning
confidence: 99%